TINGKAT SENSITIFITAS LAMPU ULTRAVIOLET UNTUK PEMERIKSAAN KLINIS INFEKSI Microsporum canis PADA ANJING - , ANNISA NURINA ASHARI, Dr. drh. Soedarmanto Indarjulianto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Microsporum canis was one of the causes of ringworm in dogs with incidence rates reaching 70% and in cats with incidence of 98%. One of the diagnostic method which is used in clinical examination of ringworm by irradiating the ringworm lesions with ultraviolet light (UV). The lesion of ringworm leads to fluorescence of yellow green due to Microsporum canis infection. The objective of the study was to compare the level of UV sensitivity toward skin of dogs infected with Microsporum canis. The sample of the study were eleven dogs and had been infected with pure cultures of Microsporum canis. Every three days interval, clinical observation was carried out by irradiation using three different UV lights, the UV-A lamp , UV-B light, and UV light C. UV-A light is known as the Wood's Lamp, and recommended by veterinarians for clinical examination ringworm. UV-B lamp is sold in the market by using AA size batteries as a source of energy. UV-C lamp is a widely used for detecting of originality of money. Before the use of UV lamp, the lamp is turned on for 3-5 minutes before examination in order to reach full radiation. The results were grouped into four groups, namely the negative category (-), one positive (+), two positive (++) and three positive (+++). UV-A light and UV-B light resulted on category negative (-) and a positive (+), respectevely . the UV-C light resulted on one positive category (+) and two positive (++). Based on the result it could be concluded that the sensitivity of the UV light was affected by two factors of UV lamps and the nature of animal factors. UV-C light was the most sensitive to clinical examination of Microsporum canis infection.